2003
DOI: 10.1289/ehp.6286
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito coil emissions and health implications.

Abstract: Burning mosquito coils indoors generates smoke that can control mosquitoes effectively. This practice is currently used in numerous households in Asia, Africa, and South America. However, the smoke may contain pollutants of health concern. We conducted the present study to characterize the emissions from four common brands of mosquito coils from China and two common brands from Malaysia. We used mass balance equations to determine emission rates of fine particles (particulate matter < 2.5 microm in diameter; P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
162
1
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(178 citation statements)
references
References 18 publications
10
162
1
5
Order By: Relevance
“…[8][9][10] Furthermore, burning mosquito coils release significant amounts of fine particulate matter and volatile organic compounds that may pose an acute and chronic risk to human health. 11 However, studies into the insecticidal activity of norchrysanthemic acid esters with high vapor activity at ambient temperature by Ujiahra and others 12 identified a synthetic pyrethroid insecticide ("metofluthrin") that doesn't require a heating source and was extremely effective at knocking down Culex pipiens pallens in the laboratory. Metofluthrin has also been shown, with aspirator collections, to provide spatial repellency to mosquitoes in outdoor shelters without walls 13,14 and in houses.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Furthermore, burning mosquito coils release significant amounts of fine particulate matter and volatile organic compounds that may pose an acute and chronic risk to human health. 11 However, studies into the insecticidal activity of norchrysanthemic acid esters with high vapor activity at ambient temperature by Ujiahra and others 12 identified a synthetic pyrethroid insecticide ("metofluthrin") that doesn't require a heating source and was extremely effective at knocking down Culex pipiens pallens in the laboratory. Metofluthrin has also been shown, with aspirator collections, to provide spatial repellency to mosquitoes in outdoor shelters without walls 13,14 and in houses.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that one mosquito coil releases the same amount of particulate matter as 75 to 137 cigarettes (8).…”
mentioning
confidence: 99%
“…There is also evidence that pesticides, including dichlorodiphenyltrichloroethane (DDT), pyrethroids, and chlorinated pesticides, may play a role in the development of childhood ALL through the deregulation of the immune system 40, 41. While we only examined broad pesticide classes in our exposure‐outcome analyses, it is important to highlight that most of the mothers who reported using insecticides inside their homes described applying them in the form of sprays (which contain predominantly pyrethroids and/or OPs) and coils [which contain pyrethroids and other carcinogenic agents such as polycyclic aromatic hydrocarbons (PAHs) and volatile organic compounds (VOCs)] 42, 43. Future studies may consider investigating the effects of specific pesticides and active ingredients on childhood leukemia in order to minimize knowledge gaps regarding the potential carcinogenic action of different pesticide groups.…”
Section: Discussionmentioning
confidence: 99%